2013
DOI: 10.1111/appy.12010
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide DNA methylation patterns in discordant sib pairs with alcohol dependence

Abstract: Introduction: Alcohol dependence is a complex disease caused by a confluence of environmental and genetic factors. Epigenetic mechanisms have been shown to play an important role in the pathogenesis of alcohol dependence. Methods: To determine if alterations in gene-specific methylation were associated with alcohol dependence, a genome-wide DNA methylation analysis was performed on peripheral blood mononuclear cells from alcohol-dependent patients and siblings without alcohol dependence as controls. The Illumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 54 publications
3
34
2
1
Order By: Relevance
“…Hypomethylation was also observed in long terminal repeat (LTR) regions of retrotransposons in the superior frontal cortex of postmortem alcohol users [56]. Other important pathways related to apoptosis [52,54,55], metabolism [53], as well as GABA and dopamine systems [40,53].…”
Section: Adulthoodmentioning
confidence: 98%
See 1 more Smart Citation
“…Hypomethylation was also observed in long terminal repeat (LTR) regions of retrotransposons in the superior frontal cortex of postmortem alcohol users [56]. Other important pathways related to apoptosis [52,54,55], metabolism [53], as well as GABA and dopamine systems [40,53].…”
Section: Adulthoodmentioning
confidence: 98%
“…In one study [52], the tumour suppressor gene BLCAP and ABR-involved in vestibular morphogenesis-were hypomethylated in heavy alcohol drinkers versus abstinent controls, suggesting one mechanism by which tumour risk may be higher in alcohol drinkers. In another study, alcohol-dependent discordant siblings showed hypomethylation of SSTR4-an important gene for hormonal function-and hypermethylation of the GABA receptor gene GABRP [53]. Finally, two EWASs measured DNAm at multiple time points: before and after a 25-day treatment programme [54], or a 12-year interim period [55].…”
Section: Adulthoodmentioning
confidence: 99%
“…Chronic alcohol consumption could be associated with altered methylation patterns of various genes acting via s-adenosylmethionine (SAM) metabolism and altering homocysteine levels. Approaches that can detect altered transcripts and corresponding changes in methylation levels peripheral blood samples such as lymphocytes and mononuclear cells can be used as potential tool for the development of biomarkers (Biermann et al, 2009; Hillemacher et al, 2009; Zhang et al, 2013; Zhao et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Other studies have found associations between alcohol dependence and CpG methylation in known candidate genes for alcohol addiction, for example: SLC6A3 (Hillemacher et al, 2009), and OPRM1 (Zhang et al, 2012). More recent studies have used arrays to show that methylation of many CpGs across the methylome are associated with alcohol dependence (Philibert et al, 2012, Zhao et al, 2013, Zhou et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Second, the sample sizes in the previous studies are small and therefore lack adequate statistical power. For example, the largest sample size reported in the extant literature was 20 sibling pairs (n=40) (Zhao et al, 2013). Third, instead of using primary human tissue, one of these studies used cell lines (Zhou et al, 2011), and another used DNA from Epstein Barr virus (EBV) transformed lymphocytes (Philibert et al, 2012), both of which may show different methylation profiles than primary human tissue.…”
Section: Introductionmentioning
confidence: 99%